Suitability of a SiPM photodetector for implementation in an automated thermoluminescent dosimeter reader. (August 2019) - Taggart, M.P.; Charoupa, A.; Hubbard, M.W.J.; Jafari, S.M.; Lohstroh, A.; Stroud, M.
Abstract: It is widely known that SiPM photodetectors have a strong temperature dependence. TrueInvivo is currently developing an automated TLD reader with the intention of replacing the PMT with a SiPM, taking advantage of the low power consumption, small form-factor, and low cost the SiPM has to offer. Here we discuss our initial investigations into the suitability of this switch in applied technology, present spectroscopic response as a function of SiPM temperature, and the effectiveness of some options to mitigate this concern. It was found that while the SiPM is indeed affected by variations in temperature a recovery of ∼ 50–60% in gain and resolution could be achieved with a rudimentary cooling system. Abstract : Highlights: Development of readout components for high spatial resolution (∼1 mm) micro-silica dosimeters. Stability of SiPM operational parameters under exposure to extreme temperatures (20–350 °C). Spectroscopic performance of a CsI(Tl)-SiPM system with respect to temperature variations. Implementation of potential temperature compensation techniques achieving a ∼50% recovery.